The association of pre‐operative home accelerometry with cardiopulmonary exercise variables. (12th December 2017) - Cui, H. W.; Kirby, G. S.; Surmacz, K.; Hargrove, C.; Griffiths, J.; Turney, B. W.
Summary: We investigated the association of pre‐operative activity, reported by the Duke Activity Score Index, Short Form‐12 and measured by an accelerometer worn at home, with five cardiopulmonary exercise variables: peak power; peak oxygen consumption; anaerobic threshold; and ventilatory equivalents for oxygen and carbon dioxide. Fifty patients scheduled for major surgery underwent a standard pre‐operative cardiopulmonary exercise test and wore a chest‐mounted triaxial accelerometer for a mean (SD) duration of 3.2 (0.4) days. The Duke Activity Score Index and six accelerometer variables were significantly correlated with all five cardiopulmonary exercise variables, Pearson correlation coefficients 0.5–0.7, p = 0.02 to p < 0.001. Our results can guide future studies that measure physical activity for pre‐operative assessment and interventions.